2008
DOI: 10.1253/circj.cj-08-0368
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Bicarbonate Improves Long-Term Clinical Outcomes Compared With Sodium Chloride in Patients With Chronic Kidney Disease Undergoing an Emergent Coronary Procedure

Abstract: Study ProtocolEligible patients were randomly assigned to the sodium bicarbonate group or the sodium chloride group. Patients allocated to the 2 groups received 154 mmol/L of either sodium bicarbonate or sodium chloride. As soon as possible after admission, the following hydration protocol was started. The initial intravenous bolus was 3 ml·kg -1 ·h -1 for 1 h, if possible, before the coronary procedure. Patients subsequently received the same fluid at a rate of 1 ml·kg -1 ·h -1 J 2008; 72: 1610 -1614 (Recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…In line with this scepticism a cohort analysis of over 32,000 patients recently reported a transitory 25% increase in creatinine from a normal baseline in up to 27% of hospitalized patients without their ever having received any contrast media [26]. On the other hand, a recently published follow-up study on one of the trials included in this analysis [6] reported a significantly lower incidence of mortality and requirement for renal replacement therapy in the group treated with sodium bicarbonate after an average observation period of 15 months, suggesting even a long-term benefit [27].…”
Section: Discussionmentioning
confidence: 92%
“…In line with this scepticism a cohort analysis of over 32,000 patients recently reported a transitory 25% increase in creatinine from a normal baseline in up to 27% of hospitalized patients without their ever having received any contrast media [26]. On the other hand, a recently published follow-up study on one of the trials included in this analysis [6] reported a significantly lower incidence of mortality and requirement for renal replacement therapy in the group treated with sodium bicarbonate after an average observation period of 15 months, suggesting even a long-term benefit [27].…”
Section: Discussionmentioning
confidence: 92%
“…A large number of drugs have been used to protect renal function after PCI, such as aminophylline (Shammas et al 2001;Rohani 2010), theophylline (Wang et al 2001), atrial natriuretic peptide (Chen 2009;Morikawa et al 2009), B-type natriuretic peptide (Zhang et al 2010), mannitol (Kelly et al 2008), prostaglandins (McCullough andTumlin 2009), N-acetylcysteine (Thiele et al 2010), sodium bicarbonate (Masuda 2008) and statins (Xinwei et al 2009); however, few of them (Kowalczyk et al 2007;Zoungas et al 2009) have shown exact protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…30, 31 Masuda et al previously reported that hydration with sodium bicarbonate reduces the incidence of renal replacement therapy and death in patients with chronic kidney disease undergoing an emergent coronary procedure. 32 A possible mechanism for the prevention of CIN with sodium bicarbonate is inhibition of oxidant injury through alkalizing renal tubular fluid. In the present study, we directly demonstrated a relationship between contrast-induced oxidative stress and chronic renal insufficiency.…”
Section: Prediction Of Chronic Renal Insufficiencymentioning
confidence: 99%